PENGARUH SUBSTITUSI TEPUNG RUMPUT LAUT EUCHEUMA COTTONI DAN TEPUNG TEMPE UNTUK PEMBUATAN PMT IBU HAMIL KEKURANGAN ENERGI KRONIS (KEK) - Tobianus Hasan,; Meliana Pamut, (Journal of Innovation Research and Knowledge, 2024)
Malnutrition is one of the symptoms of Chronic Energy Deficiency (Fetal health can be threatened due to the impact of KEK which is severe in pregnant women. Babies with low birth weight as well as premature babies are more likely to suffer from a variety of diseases including infections, respiratory problems, and the possibility of death. In addition, newborns with this disorder are also at risk of growth and development problems, especially brain development problems. One of thepreventionof chronic energy deficiency (SEZ) by providing functional food ingredients developed is the substitution of eucheuma cottoni seaweed flour and tempeh flour, which has a high energy content that can overcome chronic energy deficiency in pregnant women.The research design used a completely random method (CRD). By substituting eucheuma cottoni seaweed flour and tempeh flour for 4 treatments. Based on the ANOVA test, the results showed that there was an effect of substitution of eucheuma cottoni seaweed flour and tempe flour on organoleptic properties (color) with a P value of 0.000 (<0.05), for (aroma) a P value of 0.000 (>0.05,) for (texture) P value 0.000 (<0.05), for (taste) P value 0.000 (<0.05) from the four treatments for aspects of color, texture, taste shows significant differences. After carrying out further tests using the Tukey test, it showed that the color aspect of P0 was significantly different from P1, P2, for aroma P0 was significantly different from P1, P2, for texture P0 was significantly different from P1, P2, P3 and for taste it was significantly different from P1, P2, P3. Based on this research, the best organoleptic test results and the panelists liked the most were P3, namely cookies with the addition of 45% seaweed flour and 20% tempeh flour. From the research results, the author recommends P3: because it has the highest nutritional content. Values ​​in nutritional analysis per slice of 65 pieces: energy 43.24 kcal, protein 1.34 grams, fat 2.59 grams, carbohydrates 3.88 grams